2018
DOI: 10.1002/cbic.201700615
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining of the Lipopeptide Biosynthesis of Paenibacillus polymyxa E681 in Combination with Mass Spectrometry: Discovery of the Lipoheptapeptide Paenilipoheptin

Abstract: Paenibacillus polymyxa strains are qualified for agro-biotechnological uses such as plant growth promotion and for biocontrol strategies against deleterious phytopathogenic competitors in the soil depending on their attractive arsenal of bioactive compounds. Moreover, they are potent producers of antibiotics for medical applications. To identify new products of such organisms, genome mining strategies in combination with mass spectrometry are the methods of choice. Herein, we performed such studies with the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 56 publications
(190 reference statements)
3
22
0
Order By: Relevance
“…Paenilipoheptin was recently identified by genome mining of P. polymyxa E681. Genome analysis of E681 revealed that the paenilipoheptin BGC is composed of five ORFs encoding the hybrid NRPS- Trans -AT-PKS (Vater et al, 2018). The first two ORFs ( phnAB ) encode Trans -AT-PKS, and the rest ( phnCDE ) encode NRPSs.…”
Section: Antimicrobial Compound Productionmentioning
confidence: 99%
“…Paenilipoheptin was recently identified by genome mining of P. polymyxa E681. Genome analysis of E681 revealed that the paenilipoheptin BGC is composed of five ORFs encoding the hybrid NRPS- Trans -AT-PKS (Vater et al, 2018). The first two ORFs ( phnAB ) encode Trans -AT-PKS, and the rest ( phnCDE ) encode NRPSs.…”
Section: Antimicrobial Compound Productionmentioning
confidence: 99%
“…While the peaks with low intensity exhibited the mass spectrum of nunamycin (m/z 1138.592) [29], putisolvin II (m/z 1436.7) [30], penta-acyl lipid A (m/z 1562.846 and 1693.901) [31] and xantholysin (m/z 1763.976, 1802.856). [32] In IMA5 (Figure 2b), the major peaks revealed the presence of fusaricidins (m/z 883.626, 897.661, 935.629, 954.715, 961.686, 968.733, 982.751 and 999.641), while the peaks with low intensity exhibited the mass spectrum of polymyxins (m/z 1191.871 and 1207.836) [33] and tridecaptins (m/z 1640.024, 1641.985 and 1655.997) [34,35]. In strains IMA4, IMA7 and IMA11 (Figure 2c), no lipopeptides were detected, as reported by [36].…”
Section: Lipopeptides Detection By Maldi-tof Ms Analysesmentioning
confidence: 99%
“…The substrate amino acid of the adenylation domain (AD) of the hybrid PKS/NRPS was predicted to be D-glycine. It should be noted that this amino acid was not previously identified in paenilipoheptin (Vater et al, 2018).…”
Section: Characterization Of the Identified Bgcsmentioning
confidence: 81%
“…genomes ( Table 2). The hits of the MIBiG database search were found to be BGC of paenilipoheptin (Vater et al, 2018), but had a low (52.0-82.0% depending on the module) sequence identity. The NaPDoS-based analysis of the ketosynthase (KS) domain of trans-AT PKS/NRPS showed that its sequence similarity with the sequences in the database was ≤59.0%.…”
Section: Characterization Of the Identified Bgcsmentioning
confidence: 99%